Using the Logit function to predict the failure or success of business organizations - Hakim Mohsen Muhammad (Iraqi Journal for Administrative Sciences, 2024)
Business organizations in a particular economy face a set of problems and obstacles, some of which result from economic factors and causes such as changes in the levels of supply and demand, a rise in prices, or being affected by inflation rates. Therefore, they are exposed to failure, which may lead to bankruptcy and liquidation (bankruptcy) sometimes, or are treated by reorganization or It achieved success in performing its required objectives. The focus of this research is to study the performance levels of a group of (12) industrial companies classified into three groups (construction, engineering, food) to detect the extent of failure or success of these companies using the Logit function.